外側ウェッジが歩行に与える影響 - 大畑 光司; 市橋 則明; 竹村 俊一 (理学療法学, 2004)
The aim of this study was to investigate the effect of a laterally wedged insole on muscle activation, center of pressure, and pelvic motion during treadmill walking. Ten healthy subjects participated in this study. They walked at 3 km/h on a treadmill with and without a laterally elevated insole. Electromyographic data from the right leg muscles, a change in foot pressure during walking, tracking of the center of pressure (COP), and a video recording of pelvic motion were simultaneously collected, and each data set was compared for walking with and without the wedge. Electromyographic analysis showed that the insole caused a significant increase in peroneous longus muscle activity from foot flat to the mid stance phase. The COP was seen to shift to the lateral side during the heel contact phase, when the insole was used. However, the COP shifted to the medial side during the terminal stance. The pelvic sway during the stance phase did not show any change. In conclusion, this study demonstrated that a laterally wedged insole caused the COP to move laterally, and to generate a change in activity of the peroneous longus. 本研究の目的は外側ウェッジが歩行中の下肢筋活動，足圧中心，骨盤の運動に与える影響について，明確にすることである。健常成人10名を対象とし，被験者にトレッドミル上を時速3kmで歩行させ，立脚期の下肢筋電図，足底圧と足圧中心移動，歩行中の骨盤中心の移動距離に生じる変化を測定し，外側ウェッジの有無により比較した。筋電図解析では，通常の歩行と比較して外側ウェッジ歩行では，長腓骨筋が立脚初期から中期にかけて有意な筋活動の増加を認めた。足圧中心は踵接地時に有意な外側変位を認め，立脚後期から有意な内側変位を認めた。しかし歩行時の側方への骨盤中心の移動には変化がなかった。本研究の結果，外側ウェッジにより，踵接地時に足圧中心を外側に変位させ，その後，腓骨筋の筋活動を増加させることが示された。